2019
DOI: 10.15171/jlms.2019.47
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Er:YAG Laser Irradiation Combined With Fluoride Application on the Resistance of Primary and Permanent Dental Enamel to Erosion

Abstract: Introduction: Erosion is an important cause of tooth mineral loss. The combined use of lasers and fluoride has been introduced as a novel modality for the prevention of enamel demineralization. This study aimed to assess the effect of Er:YAG laser combined with fluoride application on primary and permanent enamel resistance to erosion. Methods: Eighty enamel specimens of permanent (n=40) and primary (n=40) molars were prepared and randomly assigned to 4 groups: C-control (no pretreatment), F-acidulated phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
3
5
0
2
Order By: Relevance
“…Since permanent teeth were harder than primary teeth, it was expected that they would be more resistant to dental erosion however, we noticed that primary teeth had a greater percent decrease of microhardness but without significance after 28 days of incubation in the different medications. That was in agreement with other studies that observed no statistically significant differences between the rate of erosion progress in primary and permanent teeth (15,25) . Whereas other studies observed that dental erosion proceeds more rapidly in primary than in permanent enamel (16,24) .…”
Section: Discussionsupporting
confidence: 94%
“…Since permanent teeth were harder than primary teeth, it was expected that they would be more resistant to dental erosion however, we noticed that primary teeth had a greater percent decrease of microhardness but without significance after 28 days of incubation in the different medications. That was in agreement with other studies that observed no statistically significant differences between the rate of erosion progress in primary and permanent teeth (15,25) . Whereas other studies observed that dental erosion proceeds more rapidly in primary than in permanent enamel (16,24) .…”
Section: Discussionsupporting
confidence: 94%
“…Deciduous tooth enamel has lower inorganic content than permanent tooth; thus, it has a lower microhardness. The mean baseline micro-hardness values of deciduous enamel samples ranged from 340.45 ± 15.62 to 345.84 ± 6.97 VHN in our study, which was in accordance with that of Molla Asadollah et al [ 24 ] Surface hardness increased after pH-cycling in all groups indicating mineral gain happened. BAG exhibited superior recovery capacity in accordance with other studies [ 25 ] since the lowest concentration of it successfully restored the surface hardness, and showed significantly higher % REMH than the DDW.…”
Section: Discussionsupporting
confidence: 91%
“…Applications of lasers in medicine have been encouraged in various fields such as dermatology, ophthalmology, dentistry, and several surgical procedures. [1][2][3] Several studies have been conducted in the field of skin treatment using the new applications of laser and selective photothermolysis over the past two decades. 4,5 The selection of laser is dependable on the heat attained in the thermophore, the depth of wavelengths that permit deeper penetration into the skin with less scattering, [6][7][8] the absorption peaks, and the localization of heat in the target that should be shorter in time than the thermal relaxation time.…”
Section: Introductionmentioning
confidence: 99%